Validated Folklore Materials for Elementary Reading Interest and Literacy: Bahan Ajar Cerita Rakyat Tervalidasi untuk Minat dan Literasi Membaca - Syam, Alif Kurnia; Syamsuri, Andi Sukri; Latief, Syekh Adiwijaya (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Reading interest and reading literacy are essential competencies in elementary Indonesian language learning because they support students’ comprehension, communication, and lifelong learning. Specific Background: Fourth grade students still face difficulties in understanding folklore texts due to limited contextual, visually attractive, and student-centered teaching resources. Knowledge Gap: Previous studies have developed folklore-based resources, yet systematic development that integrates local cultural content, expert validation, practicality testing, and field-based literacy measurement remains limited. Aims: This study developed Indonesian language teaching materials on folklore to support fourth grade students’ reading interest and reading literacy. Results: The developed printed folklore materials were categorized as very valid, with media expert validation reaching 96% and material expert validation reaching 98%. Practicality testing showed very high results through learning implementation and teacher responses with a score of 97, while student responses reached 89%. Student reading literacy increased from a pretest mean of 70.71 to a posttest mean of 80.29, and reading interest increased from 57.29 to 89.76. Novelty: The study presents locally grounded folklore teaching materials supported by illustrations, reading guidance, vocabulary support, and literacy exercises designed for elementary learners. Implications: These findings indicate that folklore-based teaching materials can serve as a contextual learning alternative for strengthening reading engagement, literacy achievement, and cultural understanding in elementary Indonesian language learning. Highlights • Expert appraisal placed the developed resource in the very valid category.• Teacher and student responses showed strong practicality in classroom use.• Posttest scores showed higher learner engagement and comprehension outcomes. Keywords Folklore Materials; Reading Interest; Reading Literacy; Elementary Students; Local Culture